Analysis of IGH allele content in a sample group of rheumatoid arthritis patients demonstrates unrevealed population heterogeneity - Hardt, Uta; Corcoran, Martin M.; Narang, Sanjana; Malmström, Vivianne; Padyukov, Leonid; Karlsson Hedestam, Gunilla B. (Frontiers in Immunology, 2023)
Immunoglobulin heavy chain (IGH) germline gene variations influence the B cell receptor repertoire, with resulting biological consequences such as shaping our response to infections and altering disease susceptibilities. However, the lack of information on polymorphism frequencies in the IGH loci at the population level makes association studies challenging. Here, we genotyped a pilot group of 30 individuals with rheumatoid arthritis (RA) to examine IGH allele content and frequencies in this group. Eight novel IGHV alleles and one novel IGHJ allele were identified in the study. 15 cases were haplotypable using heterozygous IGHJ6 or IGHD anchors. One variant, IGHV4-34*01_S0742, was found in three out of 30 cases and included a single nucleotide change resulting in a non-canonical recombination signal sequence (RSS) heptamer. This variant allele, shown by haplotype analysis to be non-expressed, was also found in three out of 30 healthy controls and matched a single nucleotide polymorphism (SNP) described in the 1000 Genomes Project (1KGP) collection with frequencies that varied between population groups. Our finding of previously unreported alleles in a relatively small group of individuals with RA illustrates the need for baseline information about IG allelic frequencies in targeted study groups in preparation for future analysis of these genes in disease association studies.